Pelatihan Penguatan Kemampuan Asesmen Kompetensi Minimum (AKM) Kelas Di SMPK Rosa Mystica - Coryunitha Panis, Isabel; Dewa, Egidius; Ki`i, Oktavianus Ama (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This article discusses the training to strengthen the minimum competency assessment (AKM) skills of seventh-grade students at SMPK Rosa Mystika in Kupang City. The training was conducted three times with a focus on improving AKM in literacy and numeracy. The implementation method involved 32 students participating in a series of activities, including pretests and posttests to measure knowledge improvement before and after the training. The evaluation results show a significant improvement in the literacy and numeracy skills of students after the training. Previously, all students were in the very low category, but after the training, 24 students reached the moderate category, and 8 students remained in the low category. This training successfully enhanced the literacy and numeracy skills of students at SMPK Rosa Mystica.